Quality of life related to the health and mood states of students in educational institutions from Antioquia, Colombia - Cardona-Gómez, Jason; Gonzalez, Victor-Manuel (Universidad y Salud, 2025)
Introduction: Even though health-related quality of life (HRQL) and mood states are key indicators of the well-being of adolescents, their relationship has not been analyzed in students from Antioquia, Colombia. Objective: To determine HRQL and mood states in schoolchildren from Antioquia. Materials and methods: A cross-sectional study was conducted on 1,957 schoolchildren and adolescents aged between 9 and 20 years. Measurements of HRQL, anxiety, depression, hostility and happiness, physical activity, sedentary behavior, parental social support, and socioeconomic status were applied. Results: A high quality of life (HQL) was observed more frequently in male participants, students with parental support, physically active, and those belonging to medium and high socioeconomic status. HQL decreased 15% as their age increased by one year. Also, HQL was reduced when depression, anxiety, and sedentary behavior increased. Furthermore, depression and anxiety levels were higher in women, older students, as well as in those without parental control and with sedentary behavior. Conclusions: HRQL is associated with mood states, physical activity, sedentary behavior, and parental support. In contrast, mood states are related to gender, parental support, HQL, and sedentary lifestyle.